Hubungan Fenomena Groupthink dengan Gaya Kepemimpinan Ketua RT di Desa Cikarawang - Distra Asniar; Sarwititi Sarwoprasodjo (Institut Pertanian Bogor, 2019)
Neighborhood activities are a process that can be used to see the level of group members' participation, often member participation is influenced by several things, such as groupthink phenomenon and group leader leadership style. The purpose of this study was to: (1) identify groupthink causal factors in groups, (2), identify leadership styles found in neighborhood, and (3) analyze the relationship of leadership style with groupthink phenomena in groups. This study uses a quantitative approach supported by qualitative data with 30 neighborhood as respondents. The subjects of this study were neighborhood groups located in Cikarawang Village, Dramaga District, Bogor Regency. Analysis of research data using the Spearman rank correlation test. The results show that there was no relationship between the leadership style of the chair and groupthink phenomena in the neighborhood activities. This condition influences the neighborhood leader dominant leadership style is laissez faire, so it has no relation to the decline in criticism of neighborhood members in groupthink phenomena.